Analisis Efisiensi Metode Tradisional dengan Metode Activity Based Costing (ABC) Terhadap Harga Pokok Produksi Pada CV. Faiz Jaya Sidoarjo - Dewi Maryam; Mychelia Champaca (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Abstract : Activity Based Costing (ABC) is a cost model that identifies activities in an organization and provide the cost of each activity resource to all the activities and services according to the actual consumption by each: the determination of indirect costs (overhead) and direct costs. In this way the company can establish the true cost of the individual products and services for the purpose of identifying and eliminating activities that do not benefit from lower prices and unfavorable activity and lower the price of activities that are too expensive. In a company, Activity Based Costing (ABC) provides enterprise resource costs through activities during construction projects and services provided to customers. It is commonly used as a tool to understand the activity and customer cost and profitability. Thus, Activity Based Costing (ABC) has been used to support strategic decisions primarily on price, the identification and measurement of the activity improvement initiatives during the project development activities. Keywords : Activity Based Costing (ABC)